Futures of Lisbon: transportation, mobility and accessibility - Ramos, M.; Alves, M, (Futuros de Lisboa (Catálogo Exposição), 2018)
Physical mobility needs energy: this is an unquestionable platitude. The hydrocarbons that have so strongly conditioned life in the last century have allowed a growing percentage of humankind to make disruptive dreams of dizzying speeds, and have induced "modern" urbanized societies to quasi-comatose states of drunkenness from consuming cheap energy. A little man will not have a clear conscience over this, but a Big Man has an obligation to integrate in his calculations the basic assumption that three tablespoons of crude is sufficient to obtain the energy of eight hours of manual labour, and that the energy present in the full fuel tank of a motor vehicle is equivalent to two years of "blood motor" activity that we are made of. It is therefore reasonable for the Little Big Man to choose the notion of "energy crisis" as a problematic pillar of analysis.